Impact of Aging and Low Temperatures on the Mechanical Properties of Low-Cost Seismic Isolator Prototypes - Isabel C. Velasco-Cuervo; Erika D. Lemos-Micolta; Ingrid E. Madera-Sierra; Manuel Alejandro Rojas-Manzano; Mario F. Muñoz-Velez; Orlando Cundumí; Edwin Patino; Manuel Salmeron-Becerra; Shirley J. Dyke; Mirian Velay-Lizancos (Buildings, 2025)
Seismic isolation systems are an effective passive protection strategy that decouples structures from ground motion. Their performance depends heavily on the elastomeric materials used, which must retain mechanical integrity under environmental stressors. In recent years, low-cost isolators made from natural and recycled rubber have gained attention as an affordable solution for protecting low-rise buildings in seismic-prone developing regions, particularly due to their environmental benefits and ease of installation. However, their long-term performance under real environmental conditions remains insufficiently explored. This study evaluates the durability of two types of low-cost seismic isolators: those made with natural rubber matrices (UN-FREIs) and those that use recycled rubber matrices (UR-FREIs). Mechanical tests were carried out before and after exposing the specimens to accelerated aging and low-temperature conditions, simulating environmental degradation. Changes in stiffness, damping, and energy dissipation were analyzed for both the rubber matrix and the scaled isolator prototypes. The findings indicate that both materials degrade over time, with recycled rubber exhibiting greater susceptibility to stiffness loss at low temperatures. Nevertheless, both isolator types maintained functional performance after aging, supporting their applicability in regions with moderate thermal variations. These results provide evidence for the feasibility of adopting low-cost isolators in low-rise buildings exposed to variable climates, while also emphasizing the need for standardized durability protocols during the design stage.